Kritik di Media Sosial dan Jerat Pidana Kasus Om Polos Banget dalam Perspektif Hukum Konsumen dan Hak Berkspresi - Kadek Ferdian Dwi Arsa (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Consumer criticism on social media is a common form of expression used to convey dissatisfaction with products or services. However, such criticism often generates controversy, especially when it is perceived to harm the reputation of a company. Although the right to freedom of expression is guaranteed by the Consumer Protection Law, in practice, this guarantee frequently conflicts with the defamation provisions outlined in the Electronic Information and Transactions (ITE) Law. The case of "Om Polos Banget" serves as a concrete example where consumer criticism led to legal charges due to allegations of defamation. This study aims to analyze the boundaries of consumer freedom of expression on social media within the context of Indonesian legal regulations and to identify the elements of defamation that may ensnare consumers. The research utilizes a normative juridical method, focusing on the analysis of relevant laws and regulations concerning freedom of expression and defamation. The results of the study indicate that while consumers have the right to criticize, there are legal boundaries that must be observed to prevent the criticism from resulting in legal action. Therefore, clearer policies are needed to ensure a fair balance between consumer freedom of expression and corporate reputation protection, as well as the importance of consumers maintaining ethical conduct when expressing criticism on social media.